2021
DOI: 10.1021/acsami.0c22336
|View full text |Cite
|
Sign up to set email alerts
|

FeCoP2 Nanoparticles Embedded in N and P Co-doped Hierarchically Porous Carbon for Efficient Electrocatalytic Water Splitting

Abstract: The design and synthesis of low-cost and efficient bifunctional electrocatalysts for water splitting are critical and challenging. Hereby, a bimetallic phosphide embedded in a N and P co-doped porous carbon (FeCoP2@NPPC) material was synthesized by using sustainable biomass-derived N- and P-containing carbohydrates and non-noble metal salts as precursors. The obtained material exhibits good catalytic activities in hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and overall water splitting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…Transition metals with partially filled d orbitals are generally the active catalytic sites in OER [ 16 , 17 , 21 , 64 ]. Recently, it has been reported that nonmetal atoms may become the active sites for catalytic reactions in theoretical studies [ 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metals with partially filled d orbitals are generally the active catalytic sites in OER [ 16 , 17 , 21 , 64 ]. Recently, it has been reported that nonmetal atoms may become the active sites for catalytic reactions in theoretical studies [ 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of high-performance and low-cost catalysts is highly desirable. Recently, cheap transition metal oxides [ 14 , 15 ], phosphides [ 16 , 17 , 18 , 19 ], nitrides [ 20 ], sulfides [ 21 , 22 , 23 , 24 ], carbides [ 25 ], etc., have been studied as emerging electrocatalysts, and many show excellent OER catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…S6 and Table S1†). Besides, the HER performance of P V -np-Ni(Al)-40 electrode exceeds some previously reported catalysts such as FeP nanosheet/Ti ( η 10 = 79 mV), 42 RuP 2 /NPC ( η 10 = 59 mV), 43 FeCoP 2 @NPPC ( η 10 = 114 mV), 44 and CoP/CN/Ni ( η 10 = 66 mV) 45 (Table S2†).…”
Section: Resultsmentioning
confidence: 45%
“…EIS was performed to record the Nyquist plots in Figure 5d to reflect the charge-transfer ability at the electrode/electrolyte interface in the electrochemical reaction. 52 Fitting by an equivalent circuit, the h-CoP@NC-700-300, h-CoP@NC-800-300, and s-CoP@NC-900-300 showed charge-transfer resistances (R ct ) of 29.96, 36.25, and 33.45 Ω, respectively (Table S3). The R ct of h-CoP@NC-900-300 was 26.72 Ω, which was lower than the ones above, proving its fast charge-transfer ability.…”
Section: Resultsmentioning
confidence: 99%